Factors associated with surgical complications in elderly patients with gastrointestinal neoplasms at the Centro Médico Naval - Paredes Terrones, Xiomara (2020)
Objective: To determine the factors associated with surgical complications in elderly patients diagnosed with gastrointestinal neoplasms at the Centro Médico Naval del Perú. Materials and methods: A retrospective cohort study and a secondary database analysis were conducted. The factors associated with postoperative complications in 245 patients diagnosed with gastrointestinal neoplasms between 2013 and 2015 were evaluated. The variables were age, frailty, vulnerability, previous diseases, tobacco smoking, calf perimeter, functional dependence, falls, polypharmacy and cancer location. Results: Twenty-nine point eight percent (29.8 %) of the patients presented surgical complications, which were more prevalent in cases of colorectal cancer (82.19 %) and an average age of 86.3 years. The most frequent complications were pain, hemorrhage, hydroelectrolytic disorders and surgical site infection. Using the adjusted regression model, the variables that showed the most significant association were presence of ≥3 previous diseases, tobacco smoking, calf perimeter <31 cm, functional dependence, falls in the last year, polypharmacy, frailty, vulnerability according to the Vulnerable Elders Survey (VES-13) and cancer located in colon/rectum. Conclusions: The predictive factors for developing surgical complications were colorectal cancer, vulnerability according to the VES-13, frailty according to the Fried frailty phenotype, polypharmacy, falls, functional dependence, thin calf perimeter, history of tobacco smoking, and presence of three or more comorbidities.